(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
Field trips play an important role in biology education, providing students with opportunities to interact with the natural world in a hands-on and immersive manner. In this article, we explore the importance of field trips in the study of biology, highlighting the various benefits they bring to the learning experience.